SYSTEMATIC LITERATURE REVIEW: PENGETAHUAN DAN PERILAKU MENGGOSOK GIGI PADA ANAK USIA SEKOLAH DASAR - Larasati, Ratih; Wahyuni, Dewi Farida; Prasetyowati, Silvia; Hadi, Sunomo (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2022)
Background: The majority of the Indonesian population already have good brushing behaviour, namely brushing their teeth every day. However, from this percentage only 2.8% brushed their teeth at the right time, namely at least twice after breakfast and before going to bed. Objective: To explain the knowledge and behaviour of brushing teeth in elementary school age children. Method: A literature review study of journal articles. The literature search was conducted from August to September 2020. Conclusions: The knowledge of brushing teeth for elementary school age children is in the sufficient category, which shows that elementary school age children have known the importance of brushing their teeth and brushing behaviour in elementary school age children, most children have brushed their teeth twice a day, but there are still children who brush their their teeth in the wrong time is at the same time as taking a bath because it is considered an easy and practical thing.